Islamisasi Tradisi Sedekah Laut Studi Kasus Desa Karangagung Kecamatan Palang Kabupaten Tuban - Azizatul Hanifah; M. Amin Nurdin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research discusses the Islamization of the tradition of Sedekah Laut (Sea Charity) in Karangagung Village, Palang District, Tuban Regency. This tradition is an expression of gratitude by fishermen for the bounty of the sea from Allah SWT and for seeking safety. The research uses a qualitative method with phenomenological approaches, and data collection through interviews, observation, documentation, literature review, and online sources. The results show that the Sedekah Laut tradition, previously known as 'Babakan', has a long history. Initial conflicts with Islamic teachings temporarily halted this tradition due to being considered polytheistic. However, since 2017, the tradition has resumed with some conditions. The name of the tradition has changed to Sedekah Laut or Tasyakuran Laut, reflecting acculturation and Islamization with terms such as 'sedekah' and 'tasyakuran'. This research is beneficial for understanding the existence and acculturation of the Sedekah Laut tradition among the fishermen community in Karangagung Village.